2000
DOI: 10.1190/1.1444745
|View full text |Cite
|
Sign up to set email alerts
|

Euler deconvolution of gravity tensor gradient data

Abstract: Tensor Euler deconvolution has been developed to help interpret gravity tensor gradient data in terms of 3-D subsurface geological structure. Two forms of Euler deconvolution have been used in this study: conventional Euler deconvolution using three gradients of the vertical component of the gravity vector and tensor Euler deconvolution using all tensor gradients. These methods have been tested on point, prism, and cylindrical mass models using line and gridded data forms. The methods were then applied to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(89 citation statements)
references
References 20 publications
0
76
0
3
Order By: Relevance
“…Various analysis techniques using gravity gradient tensors have been suggested and discussed (e.g., Zhang et al 2000;Beiki 2010;Martinez et al 2013;Cevallos 2014;Li 2015). These are considered to be so-called inversion techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Various analysis techniques using gravity gradient tensors have been suggested and discussed (e.g., Zhang et al 2000;Beiki 2010;Martinez et al 2013;Cevallos 2014;Li 2015). These are considered to be so-called inversion techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, differentiation of the analytic signal amplitude may amplify high frequencies. Zhang et al (2000) employed the Euler's homogeneity equation for interpretation of GGT data and showed that the standard Euler deconvolution can be extended to where B x , B y and B z are the regional values of components of gravity vector g x , g y and g z to be estimated. Their method uses the full GGT and the components of the gravity vector to provide additional constraints on the Euler solutions.…”
Section: Euler Deconvolution Techniquementioning
confidence: 99%
“…• Tensor Euler (Zhang, 2000), a 3D tensor Euler solution of the gridded data to solve for target source location.…”
Section: Data Processing and Inversionmentioning
confidence: 99%